#TITLE_ALTERNATIVE# - SUGAMA (NIM 13601006), AGUS
Sotong AUV (Autonomous Underwater Vehicle) is one of six underwater vehicle which has developed under joined ITB and BPPT. Sotong AUV was designed for underwater surveillance mision. To support that mission, understanding about the vehicle's dynamic characteristic along it's operation is very important. According to this understanding, control system can be well designed to get successful mision. In this final project, stability analysis has done after build the dynamic model based on AUV equation of motion in six degree of freedom. The dynamic model is state space equation as a result of linearization in vertical plane equation of motion. Stability analysis has done in several vehicle's operation condition involve velocity and depth. From stablity analysis, some point of operation that have low stability and unstable operation point have known. The next step was pitch damper control system design for both low stability and unstable point. After that, pitch attitude hold syatem was designed based on the dynamic model which has added pitch damper SAS (stability augmentation system) above. The control design methode was classical methode with proportional gain. The design result were successful if fulfill design criterion which has determined.